Two studied metropolitan cities in Ethiopia and their current integrated infrastructure plan to enhance resilience and sustainability - Geremew Worku; Dagnachew Adugna (Environmental and Sustainability Indicators)
As urbanization accelerates globally, cities face increasing challenges related to infrastructure development, especially in metropolitan areas central to economic and social activities. The main objective of this study is to assess the effectiveness of the current integrated infrastructure planning in in Addis Ababa and three selected sub cities of Sheger (Burayu, Galan, and Furi), focusing on their potential to improve urban sustainability and resilience. The study employed a mixed-methods approach, utilizing both descriptive and explanatory research designs. We used a purposive sampling method to get a sample that represents the group well. This included 69 respondents, 15 key interviews, and 90 focus group discussions (FGDs). We processed, coded, classified, and input the data into Microsoft Excel for analysis. The study identifies significant gaps in current planning approaches, notably the tendency to treat urban systems in isolation. It underscores the critical roles of governance, stakeholder collaboration, and efficient resource allocation in overcoming these challenges. The research looks at Addis Ababa and Sheger to find ways to improve city infrastructure. It identifies strategies, challenges, and opportunities to make the cities stronger and more sustainable. Key findings indicate substantial gaps in governance, lack of institutional collaboration, critical gap in the regulatory frameworks, Proper drainage system, gap in waste management, inefficiencies in the transportation system, poor accessibility, absence of an integrated transport plan between the cities, and lack of existing institution managing the common transport infrastructure. These insights provide actionable recommendations for city administrations, policymakers and urban planners.